PERKEMBANGAN PEMIKIRAN DAN PERADABAN DALAM ISLAM - Bunyamin, Ubun; Widi Fuzi Widayanti Ikrima; Permana Sidik; Nurlaila Fitri; Masripah; M. Tajudin Zuhri; Nenden Munawaroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Since the era of the Arab nation before Islam until today, the journey of Islamic thought and civilization has experienced various dynamics, both progress and decline. The development of Islamic thought has influenced the growth of Islamic civilization in various parts of the world, and vice versa. This shows how close the relationship is between Islamic ideas and civilization. This research method uses literature. Literature research involves collecting information and data from various sources found in libraries, including books, periodicals, notes, historical records, and more. The results of this study show that the development of Islamic thought and civilization has a reciprocal relationship, where developing thought drives the progress of civilization, while advanced civilization helps to fertilize Islamic thought. Understanding this journey is key to ensuring the contribution of Muslims to the modern world.